Methods for assessing cardiac myofilament calcium sensitivity - Dowrick, Jarrah M.; Taberner, Andrew J.; Han, June-Chiew; Tran, Kenneth (Frontiers in Physiology, 2023)
Myofilament calcium (Ca 2+ ) sensitivity is one of several mechanisms by which force production of cardiac muscle is modulated to meet the ever-changing demands placed on the heart. Compromised Ca 2+ sensitivity is associated with pathologies, which makes it a parameter of interest for researchers. Ca 2+ Sensitivity is the ratio of the association and dissociation rates between troponin C (TnC) and Ca 2+ . As it is not currently possible to measure these rates in tissue preparations directly, methods have been developed to infer myofilament sensitivity, typically using some combination of force and Ca 2+ measurements. The current gold-standard approach constructs a steady-state force-Ca 2+ relation by exposing permeabilised muscle samples to a range of Ca 2+ concentrations and uses the half-maximal concentration as a proxy for sensitivity. While a valuable method for steady-state investigations, the permeabilisation process makes the method unsuitable when examining dynamic, i.e., twitch-to-twitch, changes in myofilament sensitivity. The ability of the heart to transiently adapt to changes in load is an important consideration when evaluating the impact of disease states. Alternative methods have been proffered, including force-Ca 2+ phase loops, potassium contracture, hybrid experimentalmodelling and conformation-based fluorophore approaches. This review provides an overview of the mechanisms underlying myofilament Ca 2+ sensitivity, summarises existing methods, and explores, with modelling, whether any of them are suited to investigating dynamic changes in sensitivity. We conclude that a method that equips researchers to investigate the transient change of myofilament Ca 2+ sensitivity is still needed. We propose that such a method will involve simultaneous measurements of cytosolic Ca 2+ and TnC activation in actively twitching muscle and a biophysical model to interpret these data.